2009
DOI: 10.4103/1319-3767.56095
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the colon

Abstract: Primary lymphoma of the colon is a rare tumor of the gastrointestinal (GI) tract and comprises only 0.2-1.2% of all colonic malignancies. The most common variety of colonic lymphoma is non-Hodgkin's lymphoma (NHL). The GI tract is the most frequently involved site, accounting for 30-40% of all extra nodal lymphomas, approximately 4-20% of which are NHL. The stomach is the most common location of GI lymphomas, followed by the small intestine. Early diagnosis may prevent intestinal perforation; however, the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
3
11
0
4
Order By: Relevance
“…Other less common modes of presentation in our series included; change in bowel habit, gastrointestinal bleeding and anorexia or loss of weight, similar to other studies published (5); (1,2,10). Some authors have reported rare cases of emphysematous colitis (14) as the first clinical manifestation, and also masquerading Crohn's disease (15).…”
Section: Discussionsupporting
confidence: 84%
“…Other less common modes of presentation in our series included; change in bowel habit, gastrointestinal bleeding and anorexia or loss of weight, similar to other studies published (5); (1,2,10). Some authors have reported rare cases of emphysematous colitis (14) as the first clinical manifestation, and also masquerading Crohn's disease (15).…”
Section: Discussionsupporting
confidence: 84%
“…The GI tract is the most common site of extranodal involvement in cases of non-Hodgkin's lymphoma (NHL), with an average incidence of 5-40% [1]. The stomach is the most common site of GI lymphoma (14-38%), followed by the small intestine [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The lymph nodes are the most common sites of extrapulmonary tuberculosis; abdominal TB comes in as sixth [5][6][7]. On the other hand, GI tract is the predominant site of extra-nodal lymphoma, with the Non-Hodgkin type (NHL) being the most common variety.…”
Section: Discussionmentioning
confidence: 99%